2012
DOI: 10.1212/wnl.0b013e31826c1a8d
|View full text |Cite
|
Sign up to set email alerts
|

Glucose metabolism, gray matter structure, and memory decline in subjective memory impairment

Abstract: The cross-sectional difference in 2 independent neuroimaging modalities indicates early AD pathology in SMI. The poorer memory performance at follow-up and the association of reduced longitudinal memory performance with hypometabolism in the precuneus at baseline support the concept of SMI as the earliest manifestation of AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
194
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(216 citation statements)
references
References 38 publications
18
194
1
3
Order By: Relevance
“…Moreover, amyloid-positive subjects performed worse on SFN-N than those who were amyloid-negative. This is consistent with results reported by Rentz and coworkers (2011) in an English speaking population with the original FNAME test and using Pittsburgh compound B-positron emission tomography (PiB-PET) 11 . We used the Spanish version of FNAME (the S-FNAME) to determine whether it was also associated with Aβ burden in subjects with SCD as demonstrated with its original version (the FNAME) 15 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, amyloid-positive subjects performed worse on SFN-N than those who were amyloid-negative. This is consistent with results reported by Rentz and coworkers (2011) in an English speaking population with the original FNAME test and using Pittsburgh compound B-positron emission tomography (PiB-PET) 11 . We used the Spanish version of FNAME (the S-FNAME) to determine whether it was also associated with Aβ burden in subjects with SCD as demonstrated with its original version (the FNAME) 15 .…”
Section: Discussionsupporting
confidence: 91%
“…It refers to the perception of memory or other cognitive problems without impairment on standardized cognitive tests. Longitudinal studies have demonstrated that cognitively healthy individuals with SCD have a [9][10][11][12] . Preclinical AD, by definition, is the identification of those clinically normal individuals with AD pathological burden.…”
mentioning
confidence: 99%
“…Even in some subjects with subjective memory impairment changes in metabolism have been observed, potentially reflecting early AD-typical pathological changes in the brain [258]. Interestingly, Reiman et al (1996) were able to demonstrate abnormalities even in APOE e4-positive subjects in younger age without any cognitive symptoms, underlining the high sensitivity of this method [259].…”
Section: Fluorodeoxyglucose-petmentioning
confidence: 81%
“…Whereas most studies have reported an association between SMCs and Ab, [3][4][5][6] others could not demonstrate this relationship. 7 Previous studies with fluorodeoxyglucose (FDG)-PET, a biomarker supposed to reflect neuronal integrity, 8 have demonstrated hypometabolism when comparing cognitively normal (CN) individuals with and without SMCs, but the results have been inconsistent as to which brain regions show hypometabolism, e.g., the precuneus, 9 parietotemporal and parahippocampal gyrus, 10 or periventricular region. 11 These inconsistent patterns of FDG-PET hypometabolism could be due to several factors, including the use of different techniques to measure SMCs.…”
mentioning
confidence: 99%